DINAMIKA GARIS PANTAI KABUPATEN INDRAMAYU, JAWA BARAT, BERDASARKAN PENAFSIRAN CITRA SATELIT - Kusnida, Dida; Astjario, P. (Pusat Survei Geologi, 2008)
Marine and coastal dynamic maps of Indramayu extracted from satellite imageries indicate the quantification of changes; those are changes of coastline, extension and the potential areas of erosion and sedimentation. The biogeochemical and hydro-oceanographic interactive processes of the up and downstream areas produce the marine and coastal physiographic of Indramayu. Therefore, the problem solving of coastal abrasion and accretion in Indramayu have to be executed through inter-sector coordination. Keywords: abrasion, accretion, coastal, coastline, satellite imageries